Idiopatía - Byers, Sam, 1979-; Martínez Muñoz, Catalina; Byers, Sam, 1979- (Madrid : Siruela, 2014)
Katherine, Daniel, and Nathan evaluate their feelings about each other in a shared world marked by such eccentricities as a mysterious cattle epidemic, an unwanted pregnancy, and a bio-domed workplace housing a perfectly engineered cornfield.
Online resource; title from ePub title page (Digitalia, viewed April 1, 2016)
Keywords: Friendship -- Fiction; Interpersonal relations -- Fiction; Black humor; Electronic books